A construction of post quantum secure and signal leakage resistant authenticated key agreement protocol for mobile communication. Issue 1 (10th October 2022) - Kumar, Uddeshaya; Garg, Manish; Kumari, Saru; Dharminder, Dharminder
Abstract: Mobile communication is very important for an individual users, enterprisers, industries, businesses, and organizations. Since the nodes communicate through a public channel, security, and privacy become essential component for mobile communication. Both key exchange and authentication are two important security attributes to establish secure communication between two parties. In the past few years, various post‐quantum secure authentication protocols have been designed, but we have found that either some of the protocols are vulnerable to stolen smart card attack, invalid login, or signal leakage attack. In this article, we have discussed how the protocol Dharminder et al (Dharminder D, Chandran KP. J Ambient Intell Humaniz Comput. 2020; 11:4089‐4100.) is vulnerable to modified version of signal leakage attack, and sometimes called improved signal leakage attack. We have also suggested a remedy over the current existing protocol suffering from signal leakage attacks. The proposed protocol is secure against quantum attacks. We have proved the security of the proposed protocol under ring learning with errors assumption. The proposed authentication and key agreement needs only two messages exchange. We have also found the proposed is efficient in terms of computation with respect to relevant protocols. Abstract : The proposed protocol is secure against signal leakage attack. The proposed protocol avoids use the long‐term private key by the server. The security of above listed protocols is based on ring learning with errors and decision ring learning with errors assumptions. The proposed protocol is much more efficient in terms of both communication and computation overheads. The proposed protocol is foreward secure. The forward secrecy means a protocol that changes session keys frequently and automatically during each new connection. This idea ensures that even if the most of session keys are revealed, then also there is minimal chance of data to be exposed.